PENERAPAN NILAI-NILAI MODERASI AL-QUR’AN DALAM PENDIDIKAN ISLAM - Ashif Az Zafi (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Religious moderation is one of the themes that has been widely discussed in the past few decades. This is an anti-thesis of various intolerance attitudes that befall many circles, whether related to politics, social, or even religion. Intolerance in religion becomes the main focus of many circles. Even the younger generation practice this attitude. This attitude of intolerance is suspected to have entered primary and secondary educational institutions, while the efforts made by many parties in anticipating this movement did not reach its main essence. Intolerance in religion is influenced more by a lack of understanding of religion correctly, though al-Qur'an mentioned many principles and moderate attitudes that can be applied in the education system in schools. To get the principles and values of moderation in the Qur’an that can be applied in the education system in schools, this study uses a thematic method introduced by Fazlur Rahman. From this method, it is produced that the values of moderation in the Qur’an accumulate in aspects of justice, openness, wisdom, and balance. These values are required to always be maintained and become a guideline to achieve the universality of Islam in action. The application of these values in education can be committed with several approaches, namely the values inculcating approach, the cognitive moral development approach, the value analysis approach, the value clarification approach, and the learning approach by doing. Through this approach, moderate attitudes are instilled that can give birth to tolerance, mutual respect, and affection between people.